Complex atheromatous plaques in the descending aorta and the risk of stroke: a systematic review and meta-analysis - Katsanos, Aristeidis H; Giannopoulos, Sotirios; Kosmidou, Maria; Voumvourakis, Konstantinos; Parissis, John T; Kyritsis, Athanassios P; Tsivgoulis, Georgios (Stroke (1970), 2014)
Proximal aortic plaques, especially in the aortic arch, have already been established as an important cause of stroke and peripheral embolism. However, aortic plaques situated in the descending thoracic aorta have recently been postulated as a potential embolic source in patients with cryptogenic cerebral infarction through retrograde aortic flow. The aim of the present study was to evaluate the potential association of descending aorta atheromatosis with cerebral ischemia. We conducted a systematic review and meta-analysis of all available prospective observational studies reporting the prevalence of complex atheromatous plaques in the descending aorta in patients with stroke and in unselected populations undergoing examination with transesophageal echocardiography. We identified 11 eligible studies including a total of 4000 patients (667 patients with stroke and 3333 unselected individuals; mean age, 65 years; 55% men). On baseline transesophageal echocardiograpic examination, the prevalence of complex atheromatous plaques in the descending aorta was higher (P=0.001) in patients with stroke (25.4%; 95% confidence interval, 14.6-40.4%) compared with unselected individuals (6.1%; 95% confidence interval, 3.4-10%). However, no significant difference (P=0.059) in the prevalence of complex atheromatous plaques in the descending aorta was found between patients with cryptogenic (21.8%; 95% confidence interval, 17.5-26.9%) and unclassified (28.3%; 95% confidence interval, 23.9-33.1%) cerebral infarction. Our findings indicate that the presence of complex plaques in the descending aorta is presumably a marker of generalized atherosclerosis and high vascular risk. The present analyses do not provide any further evidence for a direct causal relationship between descending aorta atherosclerosis and cerebral embolism.